Tight Junctions and Cancer: Targeting Claudin-1 and Claudin-4 in Thyroid Pathologies - Jędrzej Borowczak; Dariusz Łaszczych; Katarzyna Olejnik; Jakub Michalski; Anna Gutowska; Monika Kula; Anita Bator; Marta Sekielska-Domanowska; Roman Makarewicz; Andrzej Marszałek; Łukasz Szylberg; Magdalena Bodnar (MDPI AG, 2024)
Purpose: Claudins are tight junction proteins partaking in epithelial-mesenchymal transition and cancer progression. In this study, we investigated the expression patterns of claudin-1 and claudin-4 in thyroid pathologies, discussed their links with the pathogenesis of thyroid cancers, and reviewed the therapeutic potential of targeting claudins in cancers. Methods: The research group 162 cores of thyroid samples from patients (70 female and 11 male) diagnosed with thyroid adenoma, goiter, papillary, medullary, and anaplastic thyroid cancers. All samples were stained for the expression of claudin-1 and claudin-4, and the analysis of IHC was performed. Results: Goiter samples showed negative claudin-1 and mostly positive expression of claudin-4. Papillary thyroid cancer and thyroid adenoma showed positive expression of claudin-1, while claudin-4 was positive in papillary thyroid cancers, goiters, and adenomas. In The Cancer Genome Atlas cohort, claudin-1 and claudin-4 were overexpressed in papillary thyroid cancer compared to normal thyroid tissues. Patients with high claudin-1 expression had significantly lower 5-year overall survival than patients with low claudin-1 levels (86.75% vs. 98.65, respectively). In multivariate analysis, high claudin-1 expression (HR 7.91, CI 95% 1.79-35, p = 0.006) and advanced clinical stage remained statistically significant prognostic factors of poor prognosis in papillary thyroid cancer. Conclusions: The pattern of claudin-1 staining was pathology-specific and changed between cancers of different histology. This phenomenon may be associated with the different pathogenesis of thyroid cancers and early metastasis. The loss of claudin-1 and claudin-4 characterized more aggressive cancers. Several studies have shown the benefits of targeting claudins in cancers, but their implementation into clinical practice requires further trials.